(untitled) (Global Journal of Management and Business Research, 2022)
The Front Office is the face of the Hotel for connecting and interacting with guests. The features of the Front Office department are Booking, Guest Relations, Check-in, and Check-out Telephone Cashier Finance. The front office is also known as the centre of the hotel. This department is located around the hotel’s foyer area and is easy for guests to find and is visible to guests, and visitors, so these are collectively referred to as the Front Office Department. Room tariff is the charge of the particular room which is sold by the front office department.